Left ventricular twist and untwist rate provide reliable measures of ventricular function in myocardial ischemia and a wide range of hemodynamic states. Issue 5 (20th October 2013) - Zhou, Wei; Benharash, Peyman; Ho, Jonathan; Ko, Yoshihiro; Patel, Nikhil A.; Mahajan, Aman
Abstract: Although rotational parameters by speckle tracking echocardiography (STE) have been previously compared to sonomicrometry and cardiac magnetic resonance imaging, few have examined the relationship between left ventricular (LV) rotational mechanics and intraventricular measures of load‐independent contractility, LV stiffness, or ventriculoarterial coupling. The aim of this study was to compare the changes in LV rotational indices to intraventricular pressure–volume (PV) relationships under a range of inotropic states induced by pharmacological interventions, acute ischemia, and changes in preload. In nine pigs, simultaneous echocardiographic imaging and LVPV measurements were performed during pharmacologically induced high or low inotropy and during acute ischemia by ligation of the left anterior descending coronary artery (LAD). Maximal ventricular elastance (Emax ), arterial elastance (Ea ), ventricular–arterial coupling (Emax /Ea ), dP/dt, tau, and other hemodynamic parameters were determined. Dobutamine and esmolol infusions led to inversely correlated changes in hemodynamic measurements of LV function. Apical but not basal rotation and diastolic rotation rate were decreased by esmolol and increased by dobutamine. The LV twist correlates well with Emax ( r  = 0.83) and Emax /Ea ( r  = 0.80). Apical diastolic rotation rate also correlates with dP/dtmin ( r  = −0.63), τ ( r  = −0.81), and LV stiffness ( r  = −0.52). LAD ligation decreased systolic and diastolic LV rotation in apical ( P  < 0.05), but not basal myocardium. Occlusion of the inferior vena cava, to reduce preload, increased apical rotation in systole and diastole. LV rotational parameters measured by STE provide quantitative and reproducible indices of global LV systolic and diastolic function during acute changes in hemodynamics. Abstract : e00110 Abstract : In this animal study, we compare the accuracy of speckle tracking‐based rotational indices and strain to intraventricular pressure–volume relationships and provide new insight into left ventricular systolic and diastolic function. Comprehensive validation of rotational indices has not been performed previously under acute hemodynamic conditions, and therefore this study provides new information regarding dynamic cardiac function.